Isolation and evaluation of Cyberlindnera fabianii strains to improve cigar tobacco leaves fermentation effect - Guo, Sida; Li, Yasen; Yang, Zhen; Zhang, Qianying; Li, Pinhe; Jiang, Zhongrong; Zhang, Jiabao; Cao, Yu; Zhang, Zhengcheng; Li, Dongliang (Frontiers in Microbiology, 2024)
IntroductionFermentation is a crucial process in cigar manufacturing. Exogenous addition of functional microorganisms for fortified fermentation can further improve cigar tobacco leaves fermentation quality.MethodsIn this study, five Cyberlindnera fabianii strains were isolated from cigar tobacco leaves. Their fermentation effects were assessed by analyzing flavor components and major chemical compositions.ResultsAmong these five isolates, four C. fabianii strains demonstrated the ability to enhance the overall flavor profile, particularly by increasing esters and chlorophyll degradation products. Additionally, several strains, particularly F3 and F4, also reduced total alkaloid and nitrogen content. Among these, C. fabianii strain F4 exhibited the most significant improvements. Sensory evaluation revealed that strain F4 could enhance mellowness, richness and sweetness while reducing irritation and off-flavors in fermented cigar tobacco leaves.DiscussionOur findings indicate that C. fabianii strain F4 can significantly improve the overall quality of cigar tobacco leaves through fermentation. This study provides a promising microbial fermentation agent for potential application in the cigar industry.